2005
DOI: 10.1117/12.638839
|View full text |Cite
|
Sign up to set email alerts
|

MRF applications: measurement of process-dependent subsurface damage in optical materials using the MRF wedge technique

Abstract: Understanding the behavior of fractures and subsurface damage in the processes used during optic fabrication plays a key role in determining the final quality of the optical surface finish. During the early stages of surface preparation, brittle grinding processes induce fractures at or near an optical surface whose range can extend from depths of a few µm to hundreds of µm depending upon the process and tooling being employed. Controlling the occurrence, structure, and propagation of these sites during subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 10 publications
0
35
0
Order By: Relevance
“…In our previous studies, the characteristics and statistical distribution of SSD as a function of different grinding processes using a polished taper technique has been measured and analyzed [14][15][16]. These results suggested that only a small fraction (1 out of tens of thousands of particles) of the abrasive particles were participating in the material removal by comparing the measured crack depth that with that expected from static indentation models.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In our previous studies, the characteristics and statistical distribution of SSD as a function of different grinding processes using a polished taper technique has been measured and analyzed [14][15][16]. These results suggested that only a small fraction (1 out of tens of thousands of particles) of the abrasive particles were participating in the material removal by comparing the measured crack depth that with that expected from static indentation models.…”
Section: Introductionmentioning
confidence: 92%
“…1). Details of this characterization technique to determine SSD depth and length distributions are provided elsewhere [14][15][16]. Photographs of the grinding setup is shown in Fig.…”
Section: Ground Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the measurement of SSD with destructive methods is complex as well as cost-intensive and time-consuming, several attempts were undertaken to correlate process parameters and measurable output values, like surface roughness. The results of Lambropoulos et al and Wang et al show, however, a broad distribution in the results of these methods [7,8]. Even though there are numerous non-destructive approaches to determine the crack depths beneath the machined surface, the destructive methods still provide the most accurate results [7].…”
Section: Introductionmentioning
confidence: 99%
“…The details of how these rules were developed are described in each of the references included in this summary (1)(2)(3)(4)(5)(6)(7)(8)(9). Figure 2 provides as a summary of some of the more commonly used rules-of-thumbs that have been developed in this study.…”
mentioning
confidence: 99%